Agriculture research in Malaysian accounting journals: some observations on studies variables - Mustafa, Hasri; Mahussin, Norlida (Zes Rokman Resources, 2018)
This article discusses the scopes associated with Malaysian accounting research into agriculture literature. The discussion is based on two renowned and widely referred Malaysian accounting journals from year 2008 to 2016, recognized as Malaysian Accounting review (MAR) and Asian Journal of Business and Accounting (AJBA). In both MAR and AJBA, Corporate Governance, Auditing and Financial Accounting Reporting were the most widely published topics. The absence of agriculture literature in these two Malaysian accounting journals was highlighted within accounting and non-accounting generalized variables. Analysis on their studied variables show AJBA provides more opportunity for other disciplines to penetrate into. The article concludes with a direction that Malaysian accounting research is leading to and a reminder of the ontological differences between agriculture studies and accounting treatise when the latter strives to meet generalization, firm attributes and professionals stereotype research.